Factors Influencing High Crime Rate in Kuala Lumpur Urban Community - Lasi, Masri bin Abdul; Yunusi, Erman bin (International Journal of Publication and Social Studies, 2020)
The research primarily aims to examine the unemployment, foreigner as well as urban poor the high crime rate for Kuala Lumpur. The urbanized city it has contributed significantly to Malaysia’s development but, simultaneously time, it has the highest crime rate per 100,000 population. Overall, 180 Questionnaire sets including printed and soft copies have been distributed and e-mailed to Kuala Lumpur respondents. A questionnaire survey based on sampling convenience is a non-probable sampling mechanism for selecting the respondents, since this approach provides researchers with the ease, availability or anyone's decision in selecting participants was using to gather data. Analysis of the data was done using Pearson correlations and liner regression techniques to identify the relationship and test hypothesis. Finally, from the perspective of policy maker and the government, both should overcome the issue in this study in a professional manner as high crime rate will increase when the social factors are increase among the urban community. The Royal Malaysian Police should improvise their tactics and strategies in order to reduce the high crime rate in Kuala Lumpur. The government also may change or make amendment certain rules and the guideline base on the situation and priority.